The Distribution of Dioscorea hispida Dennst. Germplasm in Terengganu and Phylogenetic Relationships of Dioscorea spp. using Internal Transcribed Spacer (ITS) - Mohd Fahmi, Abu Bakar; Abd Manaf, Ali; Munirah, Samsuddin (2014)
Dioscorea hispida Dennst. is a source of carbohydrates and is also important for medicinal purposes. However, the distributions and phylogenetic relationships of D. hispida were not-well documented in the state of Terengganu. D. hispida germplasms were collected from the seven districts of Terengganu between the months of April 2012 to June 2012. During the samplings and survey, a few of the eco-physiological parameters were measured such as the intensity of light, humidity and temperature as well as chlorophyll content. The locations of the distribution of D. hispida were mapped using the DIVA-GIS software. Subsamples of seven accessions were used for DNA fingerprinting. In phylogenetic analysis, these D. hispida germplasms were subjected to PCR amplification using DNA barcode such as internal transcribed spacer (ITS). The results of this study showed the distribution of D. hispida was mostly located near the rivers whilst the generated marker ITS discovered was not a suggested marker for the phylogenetic analysis of Dioscorea spp.